PELAKSANAAN SANKSI KEBIRI KIMIA BAGI PELAKU PEDOFILIA DALAM PERBANDINGAN HUKUM POSITIF DAN HUKUM INGGRIS - NIM. A1011211062, SAHRUL GUNAWAN (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract This research aims to analyze the implementation of chemical castration sanctions against pedophilia offenders through a comparative study between Indonesian positive law and English law. The study focuses on five key aspects: legal basis, type of sanction, implementation procedure, judicial decisions, and supervision mechanisms. The research employs a normative juridical method with a comparative legal approach, using literature review from both primary and secondary legal sources. The findings indicate that in Indonesia, chemical castration is regulated under Law No. 17 of 2016 on Child Protection and further elaborated through Government Regulation No. 70 of 2020 concerning the Procedures for Implementing Chemical Castration, the Installation of Electronic Detection Devices, Rehabilitation, and the Disclosure of Offenders' Identities. The implementation is mandatory based on court decisions and primarily retributive in nature, though it faces criticism related to human rights concerns and rehabilitative effectiveness. In contrast, the United Kingdom regulates sexual offences, including pedophilia, under the Sexual Offences Act 2003. The approach is medical and rehabilitative, where chemical castration is carried out voluntarily as part of a hormonal treatment program supervised by healthcare and criminal justice authorities. This method emphasizes recidivism prevention through offender rehabilitation. The study concludes that Indonesia